Analisis Fungsi Joshi Ni dalam Buku Teks Shin Nihongo No Kiso I dan Shin Nihongo No Kiso II - Zia Ul Haq; Hendri Zalman; Meira Anggia Putri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2018)
This research aimed to know function of Joshi Ni in the Shin Nihongo no Kiso I and Shin Nihongo No Kiso II’s textbook. The type of this research is qualitative and the method is descriptive. The steps of this research is (1) classified the function of joshi ni from the textbook Shin Nihongo No Kiso I and Shin Nihongo No Kiso II, (2) classified the data from the textbook based on theory that we use. The function of joshi ni based on theory that we used is divided into nineteen function. Based on analysis data, we found seventen from nineteen function. The fuctions are 19 sentences the function of joshi ni to show place of existence, 14 sentences the function of joshi ni to tell the purpose of activity, 13 sentences to tell time,12 sentences the function of joshi ni to tell recipient,11 sentences of the function of joshi ni to tell where the activity happen,8 sentences of the function of joshi ni the origin of a thing, 6 sentences of the fuinction of joshi ni to tell about respectful language, 6 sentences of the function of joshi ni to tell about unilateral action, 5 sentences of the function of joshi ni the tell about departure place,4 sentences of the function of joshi ni to to tell about ride something ,4 sentences the function of joshi ni to tell about pasive verb, 4 sentences of the function of joshi ni to tell about the result of activity, 1 sentences to tell about verb with no activity, 1 sentences to tell about total, 1 sentences to tell attitude towards something, 1 sentences to tell reasonsKeywords: Analysis, joshi ni